A relação, na atividade docente, de professores de um curso de pedagogia com o computador - Mortarello, Luciana Cicutto (2008)
The application of Information and Communications Technology (ICT) in the educational area, as a support tool to the learning process, reveals itself as a challenge for both teachers/professors and the educational community. Its insertion in the process transforms the teacher/professor s role since he/she becomes a mediator in the learning process. Due to the concern related to teacher/professor s education in order to function within this new school context, this study focuses its proposition on the relationship of professors of a pedagogy course with the computer during their teaching activity. Five professors belonging to graduate schools from the city of São Paulo took part in this study. The data was collected through testimonials. The first testimonial was written and took the following order: "What is your relationship with the computer as lecturer in the past, today and in the future. In order to have professors disclose in detail the affection perceived in the presented situations in the first testimonial, a second one was requested, and this time an oral testimonial was given. From data analysis, it was possible to note that the relationship of these professors with the computer is currently friendly since they are used to the computer in both their private lives and professional life as lecturer however, not as a support tool for the learning process. The path, nevertheless, shows that this relationship has not always been an easy one, since, at first, most professors had faced hardships to learn computer usage and its resources. The result of this research points out to the fact that if they have a greater demand as to the in-depth use of the computer as a facilitating tool of the learning process, they may respond positively. However, the graduate schools must not simply establish policies for the acquisition of resources but go beyond and offer to professors and students some preparation and motivation to reach such goal